Medical brain drain, a critical challenge to Pakistan’s healthcare sector - Amna Ahmed; Aribah; Muhammad Ibrahim (Journal of the Pakistan Medical Association, 2024)
Madam, Medical brain drain describes a condition where highly skilled healthcare workers leave their country of origin to work overseas in search of better working conditions, higher pay, or more opportunities for career advancement leading to deprivation of medical professionals and a loss of expertise and talent (1). Unfortunately, the exodus of skilled individuals from Pakistan is jeopardises country’s intellectual assets and demands immediate attention. Skilled healthcare workers shortage is worsening in Pakistan due to the high number of talented professionals migrating for better career opportunities in the foreign land. According to the Bureau of Emigration and Overseas Employment in 2022 alone, approximately 765,000 Pakistanis, including 2,500 physicians, left the country, highlighting the severity of the situation (2) The medical profession is highly regarded in Pakistan and attracts a significant number of people. Despite this, Pakistan is among the 57 countries that lack sufficient human health resources to fulfil its healthcare requirements and objectives. The country is confronted with a considerable discrepancy in the ratio of doctors to patients which stands at 1:1300, significantly below the ratio of 1:1000 recommended by the World Health Organization (WHO) (3) The degradation of the healthcare system, shortage of residency positions and lower salaries during a period of high inflation, coupled with cultural biases and undervaluation of professions like nursing have led to a shortage of healthcare staff. Moreover, societal expectations for women to prioritize their domestic duties contribute to the disproportionate number of female doctors leaving the medical field. This further burdens the healthcare system by increasing the workload for the remaining healthcare professionals (4) Brain drain hampers economic growth and innovation by robbing the nation of its skilled professionals and their expertise. This issue can be addressed by adopting a comprehensive approach such. Improving the healthcare infrastructure and working conditions, increasing residency positions and salaries and providing better job opportunities could help retain competent doctors. Encouraging research on brain drain can aid policymakers in developing tailored policies based on the country’s needs. These measures can help Pakistan build a robust healthcare system and provide quality medical services to its people.